2016
DOI: 10.1158/1541-7786.mcr-16-0223
|View full text |Cite|
|
Sign up to set email alerts
|

Heparanase Promotes Glioma Progression and Is Inversely Correlated with Patient Survival

Abstract: This study aims to target both the malignant brain tumor cells per se and their microenvironment by changing the level of an enzyme, HPSE, that breaks down modified sugar chains on cell surfaces and in the extracellular space. Mol Cancer Res; 14(12); 1243-53. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…In multiple myeloma HPSE promotes tumor cell adhesion and invasion via SDC1 ectodomain shedding and subsequent alterations in receptor tyrosine kinase signaling and integrin binding (10,23,54). Few studies have investigated the role for HPSE in primary brain tumors (2831,46), but the data suggest HPSE can promote tumor growth and progression in vivo. HPSE knockdown in human GBM43 cells cultured under neural stem cell conditions did not alter proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In multiple myeloma HPSE promotes tumor cell adhesion and invasion via SDC1 ectodomain shedding and subsequent alterations in receptor tyrosine kinase signaling and integrin binding (10,23,54). Few studies have investigated the role for HPSE in primary brain tumors (2831,46), but the data suggest HPSE can promote tumor growth and progression in vivo. HPSE knockdown in human GBM43 cells cultured under neural stem cell conditions did not alter proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…HPSE knockdown in human GBM43 cells cultured under neural stem cell conditions did not alter proliferation. The role for HPSE in proliferation in vitro may be complex and potential modifiers include cell culture conditions, cell lines used, and method to alter HPSE levels (31,46). In human GBM, HPSE is most highly expressed in the mesenchymal GBM subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, from candidate-based analyses of individual ECM components, it is known that significant increases in HSPG production occur in gliomas (Lemjabbar-Alaoui et al, 2015; Wade et al, 2013). These macromolecules can serve as a reservoir for heparin-binding angiogenic growth factors, such as fibroblast growth factors (FGFs) and VEGFs, which are subsequently released in a localized manner by heparanase (Kundu et al, 2016). Vessel-associated macromolecules, which are upregulated on the glioma vasculature include tenascin C (TNC) and periostin (Brosicke and Faissner, 2015; Mustafa et al, 2012), which interestingly are also critical niche factors for promoting cancer cell survival (Oskarsson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…HPSE expression is elevated and associated with clinical characteristics in several types of carcinomas in addition to breast cancer [4752]. For example, a meta-analysis of 27 studies confirmed that HPSE expression was correlated with clinicopathological features in gastric cancer patients [53].…”
Section: Discussionmentioning
confidence: 99%